Can Sound Corporate Governance Alleviate Corporate Failure? A Study of the Zimbabwean Financial Services Sector - Banele Dlamini; Julius Tapera; Shynet Chivasa (Journal of Economics and Behavioral Studies, 2017)
This study, using the Ordinary Least Squares (OLS) Regression Model, investigated the extent to which good corporate governance practices can minimise or alleviate corporate failure in the Zimbabwean Financial Services Sector. The results of the study reflected that sound corporate governance has a positive effect on corporate success and can alleviate corporate failure. It is thus recommended that financial institutions continuously adhere to sound corporate governance practices to guarantee corporate success and alleviate the collapse of financial institutions as has been witnessed in the past. The findings of the study will assist policy makers, regulators and players in the financial services sector to adhere to sound corporate governance practices, given its impact on corporate success. Further research could be carried out with regards the implementation of sound corporate governance in parastatals, quasi-government institutions and private sector companies in other sectors other that the financial services sector and how it can be monitored or enforced.